The Treatment of Depression in Patients with Heart Failure - Dominika Bachurska; Jakub Marek; Oliwia Grygorczuk; Zuzanna Czach (Kazimierz Wielki University, 2024)
This narrative review critically examines the utilization of Selective Serotonin Reuptake Inhibitors (SSRIs) in managing coexisting depression and heart failure (HF), integrating findings from various studies, clinical trials, and observational data. SSRIs, pivotal in treating mood and anxiety disorders by elevating synaptic serotonin levels, have been observed to potentially impact cardiovascular health. Specifically, SSRIs like sertraline show promise in enhancing endothelial function and exerting anti-inflammatory effects, which are beneficial in conditions like HF with preserved ejection fraction (HFpEF). Furthermore, SSRIs demonstrate favorable outcomes in reducing platelet aggregation and modulating the renin-angiotensin-aldosterone system (RAAS), suggesting a multifaceted role in HF management. However, their safety profile, particularly concerning bleeding risks, QTc prolongation, and drug interactions, necessitates careful consideration. Despite theoretical and molecular evidence supporting SSRIs' beneficial effects in HF, clinical data remain inconclusive, highlighting the need for further research. This review aims to provide a comprehensive understanding of SSRIs' effectiveness, safety, and potential benefits in treating depression and HF, offering insights for evidence-based decision-making and future research directions.